Optimization of cutting temperature and surface roughness in CNC turning of Ti-6Al-4V alloy using response surface methodology - Shazzad Hossain; Mohammad Zoynal Abedin; Rotan Kumar Saha; Md Touhiduzzaman; Md Jakir Hossen (Heliyon)
This study investigates the optimization of cutting conditions for machining titanium alloy (Ti-6Al-4V) using Response Surface Methodology (RSM), with the goal of minimizing tool-chip interface temperature and surface roughness. The research focuses on key cutting parameters to investigate the most effective combinations for enhancing surface finish and reducing thermal impact during machining. The present study deals with the dry turning of Ti-6Al-4V alloy with carbide alloy inserts in a way to utilize the Analysis of Variance (ANOVA) to develop predictive models for minimum surface roughness and optimum temperature. The findings reveal that both cutting speed and depth of cut are critical in determining machining outcomes. Specifically, a low cutting speed of 88 m/min coupled with a high depth of cut of 0.20 mm was found to elevate the cutting temperature to approximately 835 °C, resulting a surface roughness of 0.59 μm. Conversely, increasing the cutting speed to 120 m/min while reducing the depth of cut to 0.10 mm significantly lowered the temperature to around 607 °C, resulting a surface roughness of 0.19 μm; thus, thereby improving surface finish and reducing thermal stress on the tool. Additionally, a 27 % reduction in cutting temperature and a minimum surface roughness of 0.19 μm were achieved with optimal settings of 120 m/min cutting speed, 0.08 mm/rev feed rate, and 0.10 mm depth of cut. The study demonstrates the effectiveness of RSM in optimizing machining parameters for optimum temperature and better surface finish in the titanium alloy machining.